A WOMAN WHO HAD A STRONG INFLUENCE ON THE POLICY OF THE OTTOMAN EMPIRE - Karimov Azizbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The scientific article provides information about the life of Kosem Sultan, who left an indelible mark in the history of the Ottoman Empire, one of the most powerful empires in the world, and his influence on the country's domestic and foreign policy.